Harmonic mitigation of grid connected 5MW solar PV using LCL Filter - Yong B.H.; Ramachandaramurthy V.K. (Institution of Engineering and Technology, 2023)
With the increase penetration of renewable energy sources such as solar being connected to the utility grid, the use of power converters plays a major role in ensuring maximum power delivered with high efficiency. Though, the usage of power converters indirectly leads to the rise of harmonic content in the distributed system with its switching mechanism for power conversion. Filters are widely used in such situation to maintain a good state of power quality. Lots of research has been carried out to propose filter design methodology. This paper presents the implementation of LCL filter in a grid model with further harmonic attenuation through resonance mitigation. The design of the proposed filters is validated by simulation results in PSCAD software. The results show that the improved design meets the standards parallel to the THD and individual harmonic limits.